REASSESSING THE ZIMBABWEAN CHIPENDANI - Kyker, Jennifer W. (International Library of African Music, 2018)
The Shona chipendani (pl. zvipendani) is among dozens of musical bows found throughout southern Africa. An understanding of where the chipendani fits into the larger space of Zimbabwe's musical and social life is markedly thin. Other than Brenner's observation that the chipendani may occasionally be played by adult men while socializing over beer, descriptions of the chipendani seldom go further than remarking on theinstrument's associations with cattle herding, and reducing it to the status of child's play. In this article, I argue that conceptions of the musical and social identity of the chipendani must be expanded beyond its conventional portrayal as a herdboy instrument, since other groups of people have been actively involved in performing the instrument. I further maintain that the social role of the chipendani extends beyond providing accompaniment for a singular activity-that of cattle herding-into other contexts. By challenging Tracey's conception of solo bow playing as "self-delectative,” my account of chipendani music opens up space for new readings of other musical bows throughout southern Africa.
Keywords: Chipendani; Musical instruments; Ritual; Shona (African people); Bow (Music); Zimbabwe; Vadzimu (Ancestral Spirits); Bira Ceremony; Herdboy; African Music; Chipendani (Instrument)